Bibliometric Analysis: Risk Management in Islamic Finance Under The Islamic Jurisprudence Framework - Primambudi, Ganjar; Jati, Jiwo Damar (Department of Islamic Economics Law, 2024)
Research Objectives: This study aims to comprehensively analyze the stakeholders who play the most role in risk management research in Islamic finance, analyze the evolution and trends in the topic to provide future research direction.Method: This study uses a bibliometric method in biblioshiny R-Studio. Observation data is taken from the Scopus database in the form of articles and English-language.Results: We found that MK Hassan is the leading author, International Islamic University Malaysia (IIUM) is the leading affiliation, the Journal of Islamic Accounting and Business Research is the leading journal, and Malaysia is the leading country. We highlight the need for further studies to develop risk management models under Islamic principles. In addition, the rapid development of Islamic finance due to the Industrial Revolution 4.0 must be balanced with technology to minimize risks in Islamic finance.Novelty: Not only analyzes the publication quantitatively, this study also reviews the most cited papers. Furthermore, the overall analysis provides insight into the future direction of research.Conclusion: The trend of research on Islamic financial risk is not consistently growing. Besides that, the citation rate also shows a downward trend. This shows a lack of research interest in this topic. Furthermore, Islamic financial risk management is still dominated by the Islamic banking sector and limited to other sectors.